2019
DOI: 10.37358/rc.19.8.7448
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical Effect of Smoking on the Response to Chemotherapy

Abstract: Improvements in early detection of cancer have led to an important decrease in mortality rates of cancer. Given the increased incidence rates and decreased mortality rates, the number of patients surviving cancer is rapidly increasing. Although cancer patients face many physical and psychological symptoms, they also continue to engage in poor health behaviors at rates similar to those of the general-healthy population. The prime example of such unhealthy behavior is smoking. The reports show that smoking rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Patients should be encouraged to stop smoking for multiple reasons. Numerous studies have shown that smoking has an adverse effect on the efficacy of chemotherapy [77]. Patients with lung cancer who continue to smoke have a reduced life expectancy compared to patients who stop smoking [78].…”
Section: Smoking Effect Of Smoking and Response To Chemotherapymentioning
confidence: 99%
“…Patients should be encouraged to stop smoking for multiple reasons. Numerous studies have shown that smoking has an adverse effect on the efficacy of chemotherapy [77]. Patients with lung cancer who continue to smoke have a reduced life expectancy compared to patients who stop smoking [78].…”
Section: Smoking Effect Of Smoking and Response To Chemotherapymentioning
confidence: 99%